Biomedical Implications of Heavy Metals Induced Imbalances in Redox Systems. (12th August 2014) - Sharma, Bechan; Singh, Shweta; Siddiqi, Nikhat J.
Abstract : Several workers have extensively worked out the metal induced toxicity and have reported the toxic and carcinogenic effects of metals in human and animals. It is well known that these metals play a crucial role in facilitating normal biological functions of cells as well. One of the major mechanisms associated with heavy metal toxicity has been attributed to generation of reactive oxygen and nitrogen species, which develops imbalance between the prooxidant elements and the antioxidants (reducing elements) in the body. In this process, a shift to the former is termed as oxidative stress. The oxidative stress mediated toxicity of heavy metals involves damage primarily to liver (hepatotoxicity), central nervous system (neurotoxicity), DNA (genotoxicity), and kidney (nephrotoxicity) in animals and humans. Heavy metals are reported to impact signaling cascade and associated factors leading to apoptosis. The present review illustrates an account of the current knowledge about the effects of heavy metals (mainly arsenic, lead, mercury, and cadmium) induced oxidative stress as well as the possible remedies of metal(s) toxicity through natural/synthetic antioxidants, which may render their effects by reducing the concentration of toxic metal(s). This paper primarily concerns the clinicopathological and biomedical implications of heavy metals induced oxidative stress and their toxicity management in mammals.